CFD Modeling and Simulation of the riser of an Industrial Residue Fluid Catalytic Cracking(RFCC)unit - Aisha , Ahmed (2012)
A 2D axi-symmetric, steady state and pressure-based model for the riser of an industrial RFCC unit was developed with ANSYS FLUENT in workbench 13.0. The Eulerian–Eulerian approach was applied to simulate the flow behavior of the two phases and the catalytic cracking reactions. The k-ε gas–solid turbulent flow per phase model was used, and the particle-level fluctuations are modeled in the framework of the kinetic theory of granular flow. Two different drag models were used separately to simulate the gas solid interaction in the riser fluidized bed. The 14-lump kinetic model was chosen to describe the complex catalytic cracking of the heavy residual feed stock. The particle volume fraction, velocity and temperature profiles, as well as product yields in the riser were analyzed and validated with results from open literature and plant data.